Sistem Informasi Manajemen Pekerjaan Panel Listrik Berbasis Web di PT. Yoel Tricitra - Krisna Wahyudi; Lily Puspa Dewi; Adi Wibowo (Jurnal Infra, 2017)
Currently, PT. Yoel Tricitra record information in Microsoft Excel and journal book for any of their works. This may causes many work meeting which should be done for integrating company information. Beside that, without use system information, data accuration processes in PT. Yoel Tricitra are not well because many factor like human error.This Application is created using HTML, PHP, JavaScript programming language, and MySQL database. Application interface is created using template of SBAdmin with Bootstrap. Exporting file to PDF feature is created using template of fpdf181.The final result of this application development is integration of company information like notes of project order, engineer’s design, works schedule, company resources information, and company reports. Users can also see some important information of company through notification in home page of their priviledge like job order and work deadlines.